2015
DOI: 10.3402/rlt.v23.27986
|View full text |Cite
|
Sign up to set email alerts
|

Practical assessment on the run – iPads as an effective mobile and paperless tool in physical education and teaching

Abstract: This paper investigates the use of iPads in the assessment of predominantly second year Bachelor of Education (Primary/Early Childhood) pre-service teachers undertaking a physical education and health unit. Within this unit, practical assessment tasks are graded by tutors in a variety of indoor and outdoor settings. The main barriers for the lecturer or tutor for effective assessment in these contexts include limited time to assess and the provision of explicit feedback for large numbers of students, complex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…The use of technology can facilitate more studentcentred and inquiry-based learning, and allow for a flipped classroom where content is covered outside of class and application and/or feedback occurs during class time (Bowen 2012;Esson 2016;Fitzgerald and Li 2015;Kubicek 2005). One of the ways in which IT has been employed in chemical education is using various technology tools for engagement and assessment, for example, Wiki, Moodle, Web 2.0, Blackboard (Ballesta-Claver et al 2011;Biasutti and El-Deghaidy 2014;Farrell and Krause 2014;Franklin and Smith 2015;Morton and Uhomoibhi 2011), allowing to organise both asynchronous and synchronous modes of interaction. Electronic tools are feasible when designing interactive course textbooks (Nilsson et al 2010), optimising different computational procedures (Young 2011), assessing learning outcome achievement and providing feedback.…”
Section: Introductionmentioning
confidence: 99%
“…The use of technology can facilitate more studentcentred and inquiry-based learning, and allow for a flipped classroom where content is covered outside of class and application and/or feedback occurs during class time (Bowen 2012;Esson 2016;Fitzgerald and Li 2015;Kubicek 2005). One of the ways in which IT has been employed in chemical education is using various technology tools for engagement and assessment, for example, Wiki, Moodle, Web 2.0, Blackboard (Ballesta-Claver et al 2011;Biasutti and El-Deghaidy 2014;Farrell and Krause 2014;Franklin and Smith 2015;Morton and Uhomoibhi 2011), allowing to organise both asynchronous and synchronous modes of interaction. Electronic tools are feasible when designing interactive course textbooks (Nilsson et al 2010), optimising different computational procedures (Young 2011), assessing learning outcome achievement and providing feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Freeman, Son, and McRobertsʼs (2015) research on creativity assessment within fashion illustration evaluations found that "the major factor limiting further creativity development in fashion programs continues to be a lack of effective evaluation and/or evaluation tools for faculty" (p. 122). Many scholars agree that there is a need to improve evaluation techniques generally in higher education (HE; Atkinson & Lim, 2013;Franklin & Smith, 2015;Freeman et al, 2015) and yet curiously, most studies on the use of technological tools to aid assessment have focused primarily on primary and secondary school use rather than its applications within HE (Chen, Lao, & Sheum 2003, Rogers et al 2005, Sharples, Corlett, & Westmancott 2002, as cited in Franklin & Smith, 2015Nikou & Economides, 2018). Notably, Mobile-Based Assessment (MBA) is an emergent research field within the broader mobile learning area, despite a gap in literature (Nikou & Economides, 2018).…”
Section: State Of the Fieldmentioning
confidence: 99%
“…I could not identify peer-reviewed published research comparing preschool or kindergarten teachers' perceptions of these two methods, but several qualitative studies document Head Start and kindergarten teachers' negative perceptions of the amount of time necessary to complete the two-step "score on paper and upload later" process (Kim, 2016(Kim, , 2018Loesch-Griffin et al, 2014). iPads and other tablets with online access to interactive rubrics may be especially advantageous when rating real-time student performance in classroom settings that make using a laptop or stationary computer impractical, such as the playground (Franklin & Smith, 2015;Howard & Melhuish, 2017;Neumann, Warrall, & Neumann, 2019).…”
Section: "Partial Supplant" Modelmentioning
confidence: 99%